Métodos de avaliação direta da força dos músculos do assoalho pélvico feminino: revisão sistemática e modelo de utilidade - Orth, Daiana Laurenci (Universidade Federal de São Carlos, 2016)
The pelvic floor muscles have an important role in supporting the abdominal viscera and also in urinary and fecal continence, also have an important role in sexual function of women. It is through the functional assessment of these muscles that is verified the efficiency of conservative treatment, for that were developed some tools, however, the dynamometer is the only one equipment which performs direct assessment of strength. The vaginal dynamometer is a device of difficult access, since most of it was developed by research groups and only one device is commercially available, but it still used only for study and research. This study is composed of a systematic review of the literature about vaginal dynamometers and a search for prior patents, to identify devices that perform direct assessment of the strength of the pelvic floor muscles to identify the technologies developed and their settings, as well as search for commercial equipment. The objective of this study was to propose a device to evaluate the pelvic floor muscles directly and objectively, from the prior art search. The objective of this study was to propose a device to evaluate the pelvic floor muscles directly and objectively, from the prior art search. Were found 13 equipments in the literature that varied in cylindrical, specular and spherical that have different dimensions in relation to the length and diameter. They have different numbers of sensors and different parameters evaluated, as well as maximum force of contraction of the pelvic floor muscles, some equipments evaluated resistance and tonus. Were found 14 patents of which eight were related to the equipment found in the literature. The patents have a less specific detail and may have more than one configuration for the same equipment. Only one commercial equipment was found, but its sale is restricted only to research, until this moment. At the end of this review, it was possible to make a proposal for intravaginal device, as well as integrating relevant characteristics to assess the direct force of the pelvic floor as well as other important aspects to evaluate the function of these muscles, and attempts to overcome some limitations of the present equipment in literature. It is concluded from the literature that the dynamometer is an important equipment to be developed because of its contribution to evaluation of treatment and greater understanding of the pathophysiology, and has great potential for innovation
Keywords: Dinamômetro de força muscular; Dispositivo; Avaliação; Muscle strength dynamometer; Device; Evaluation; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DO ESFORCO